Recent perspectives on the synergy of mesenchymal stem cells with micro/nano strategies in peripheral nerve regeneration-a review - Sharifi, Majid; Kamalabadi-Farahani, Mohammad; Salehi, Majid; Ebrahimi-Brough, Somayeh; Alizadeh, Morteza (Frontiers in Bioengineering and Biotechnology, 2024)
Despite the intrinsic repair of peripheral nerve injury (PNI), it is important to carefully monitor the process of peripheral nerve repair, as peripheral nerve regeneration is slow and incomplete in large traumatic lesions. Hence, mesenchymal stem cells (MSCs) with protective and regenerative functions are utilized in synergy with innovative micro/nano technologies to enhance the regeneration process of peripheral nerves. Nonetheless, as MSCs are assessed using standard regenerative criteria including sensory-motor indices, structural features, and morphology, it is challenging to differentiate between the protective and regenerative impacts of MSCs on neural tissue. This study aims to analyze the process of nerve regeneration, particularly the performance of MSCs with and without synergistic approaches. It also focuses on the paracrine secretions of MSCs and their conversion into neurons with functional properties that influence nerve regeneration after PNI. Furthermore, the study explores new ideas for nerve regeneration after PNI by considering the synergistic effect of MSCs and therapeutic compounds, neuronal cell derivatives, biological or polymeric conduits, organic/inorganic nanoparticles, and electrical stimulation. Finally, the study highlights the main obstacles to developing synergy in nerve regeneration after PNI and aims to open new windows based on recent advances in neural tissue regeneration.